A Systematic Study of Antibacterial Silver Nanoparticles: Efficiency, Enhanced Permeability, and Cytotoxic Effects - Paez-Collio, M; Paez-Collio, M; Cerda-Villablanca, E; Azocar-Guzman, M; Azocar-Guzman, M; Tamayo-Villarroel, L; Tamayo-Villarroel, L (Kluwer Academic Publishers, 2014)
We report here a systematic study of the antibacterial behavior of silver nanoparticles coated with fatty acids (oleic: AgNP-O, linoleic: AgNP-L, and palmitic acids: AgNP-P) in water. We have found remarkable differences in their capability to penetrate bacteria cell over a broader range of particle size of ~4–96 nm compared to previously reported work, and a variable toxicity depending on the particles size. Our results indicate that silver nanoparticles stabilized with oleic acid showed clear advantages in antibacterial activity, penetration inside the bacteria cells, cytotoxicity, time effectiveness, efficiency, and stability against light. © 2014, Springer Science+Business Media Dordrecht.